Manual de funcionamiento, mantenimiento y aplicación pedagógica de una licuadora semi industrial en el laboratorio de investigación de cárnicos de la carrera de agroindustria de la Universidad Técnica de Cotopaxi. - Aguirre Mogollón, Fabricio Saúl (2022)
The purpose of this research study was to develop a manual for the operation, maintenance, and pedagogical application of a semi-industrial blender in the meat research laboratory of the Agroindustry career of the ‘Universidad Técnica de Cotopaxi’. During the development of this research study, it was considered to know the correct operation and use of the semi-industrial blender is relevant to the knowledge within the actions to be performed in the laboratory, with the purpose of having a guide that responds to the eventualities that can occur in the use of the equipment. Each manual contains a detailed description of the operation, its components, generalities, the steps required for correct functioning, types of maintenance that are given by the time of use, the technique to perform this action is presented in the manual, in order to work properly and prolong its useful life, the safety measures that must be carried out by the staff in charge are specified, in order to help both teachers and students to carry out the pedagogical practices on an effective way. Verifying the correct operation and usefulness of the semi-industrial blender through a demonstrative pedagogical practice based on the preparation of smoked and cured bacon, where the device was put into practice in the making of the brine for the subsequent marinade.